EMC Modelling Strategy For Automotive Applications - Englmaier, Armin; Scholl, Bernd; Weigel, Robert; Russer, Peter (IEEE 29th European Microwave Conference, 1999)
One of the main problems in simulation of high frequency electromagnetic interference in vehicles are caused by the complexity of chassis and harness. The harness with its overall wire length of several kilometers, its small cross-section diameter compared to its length and its tolerances in geometry and electrical parameters limits the application of the EMC simulation. The complexity of the problem can be modelled by using a method incorporating equivalent current sources. Hereby, the complex harness is represented by coupled transmission line systems, and the current distribution along the wires is calculated based on network theory techniques. From the current distribution equivalent current sources are derived and implemented into a 3-dimensional field solver to compute the emission to the antenna. The validity of the method is shown by way of a simple example within a complex car body.
elib2cris::1512001600,englmaier1999